Air pollution in India: a comprehensive review on impacts, challenges and mitigation strategies - Naik, Gaurav R.; Shah, Anuradha K. (International Journal Of Community Medicine And Public Health, 2025)
Air pollution is a significant challenge in India, driven by industrial emissions, vehicular exhaust, urbanization and biomass burning. It is linked to severe health impacts, including respiratory diseases, cardiovascular disorders and premature mortality, with marginalized communities bearing disproportionate burdens. India is home to nine of the world’s ten most polluted cities, with Delhi exemplifying the crisis due to stubble burning and high vehicular density. Air pollution’s economic and health costs are immense, affecting GDP and public health expenditure. Effective mitigation strategies involve technological advancements such as electric vehicles, renewable energy and IoT-enabled real-time monitoring systems. Regulatory interventions like the National Clean Air Programme (NCAP) and the adoption of Bharat Stage VI standards aim to curb pollution. International examples from China, the US and the EU provide valuable lessons on integrated policies and public participation. Future directions include leveraging AI and big data analytics for pollution management and incorporating air quality concerns into urban planning. Public awareness campaigns and grassroots movements remain essential in driving behavioral changes for sustainable practices.